2010
DOI: 10.1590/s0102-09352010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Leucogram and serum acute phase protein concentrations in queens submitted to conventional or videolaparoscopic ovariectomy

Abstract: Thirty health queens were submitted to ovariectomy by conventional technique or by videolaparoscopy. In order to study the intensity of inflammatory response by means of acute phase protein analysis and white blood cell count, serum samples were taken before and until 144 hours after the surgical procedures. The protein concentrations that were significantly increased 24 hours after surgical procedures were: ceruloplasmin, hemopexin, haptoglobin, and 1 -acid glycoprotein, 69.8%, 103.5%, 117.3%, and 199.0%, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…Alves et al 23 compared laparoscopic ovariohysterectomy using three forceps techniques; their neutrophil enumeration results conlicted with ours. However, these results may be because the open technique performed is more traumatic.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Alves et al 23 compared laparoscopic ovariohysterectomy using three forceps techniques; their neutrophil enumeration results conlicted with ours. However, these results may be because the open technique performed is more traumatic.…”
Section: Discussionsupporting
confidence: 78%
“…17 However, in a study of cats, a postoperative increase in APPs was observed in the laparotomy group compared with cats that underwent laparoscopy. 23 This group used a long-incision open technique and did not report the surgical time. In cats, open ovariectomy could be inherently less invasive, and the duration of surgery could be a crucial factor in minimising tissue trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In this group, there a peak followed by a decrease in white blood cell count was observed within 24 h, while in the laparoscopy group the peak was observed 12 h after surgery. Values with different small letters in a row and with different capital letters in a column are statistically significant at p<0.05; (ALVES et al, 2010).…”
Section: Acute Phase Protein Response and Clinical Application In Vetmentioning
confidence: 97%
“…A study was performed by Alves et al, (2010) in queens after ovariectomy by laparoscopy and conventional technique in order to verify the intensity of the inflammatory response by assessing acute phase protein and leukocyte levels. Analyses of collected blood samples were done before and until 144 hours after the surgical procedures.…”
Section: Acute Phase Protein Response and Clinical Application In Vetmentioning
confidence: 99%
“…High concentrations of major APP are usually related with infectious diseases, usually a systemic bacterial infection or an immunemediated disease (CERÓN et al, 2008;TROÌA et al, 2017). Even though APP should be analyzed together with white blood cell and neutrophil counts, they are the most sensitive in detecting inflammation and infection earliest in time (CERÓN et al, 2008;ALVES et al, 2010). However, the specificity of these proteins is low in detecting the cause of the process, being also increased in physiological states, such as pregnancy (PALTRINIERI et al, 2008).…”
Section: Acute Phase Proteins In Feline Diseasementioning
confidence: 99%